Short-Term Storage Does Not Affect the Quantitative Yield of Mycobacterium tuberculosis in Sputum in Early-Bactericidal-Activity Studies - Kolwijck, Eva (American Society for Microbiology, 2013)
Early-bactericidal-activity (EBA) studies measure the change in mycobacterial load in sputum over time to evaluate antituberculosis drugs. We investigated whether a delay in sputum processing influences the quantitative results of sputum mycobacterial culture. We identified pretreatment smear-positive sputum samples collected overnight and processed at a single laboratory. Sputum volume, time from sputum collection to processing, CFU counts/ml of sputum, and time to culture positivity (TTP) data were retrieved. We obtained 817 TTP and 794 CFU results from a total of 844 sputum samples. Contamination did not occur more frequently with prolonged storage (TTP, 2.0%; CFU, 2.4%). Sample volumes were <5 ml in 5%, 5 to 10 ml in 46%, and >10 ml in 49%. Delays to processing were 0, 1, 2, and 3 days in 696 (43.2%), 722 (44.8%), 128 (7.9%), and 65 (4.0%) samples, respectively. TTP and CFU did not significantly differ between days of delay to processing (P = 0.098 and P = 0.908, respectively), but there was a nonsignificant trend toward a prolonged TTP over time (P = 0.052, Jonckheere-Terpstra trend test). Sputa of <5 ml in volume showed a significantly prolonged TTP compared to sputum of >5 ml (113 h versus 99 h; P < 0.01) but no significant decrease in CFU. Sputum can be stored under refrigerated conditions for deferred processing for at least 3 days. This means that central laboratories can be used for quantitative mycobacterial study endpoints when delays to processing are not expected to exceed a few days. Care should be taken to collect sputum of sufficient volume.